Possibilities for improving energy efficiency in industry sector utilizing low temperature waste heat recovery - Shesho, Igor; Markov, Zoran; Tashevski, Done; Dimitrovski, Dame (Balkan Environmental Association (B.EN.A.), 2018)
The energy efficiency in the industry sector is a strong and leading factor for the competitiveness on the domestic and foreign markets. In this paper are analysed the possibilities for improving energy efficiency in the industry sector by utilising low temperature waste heat recovery (LTWHR). As a waste heat it is considered the energy that is generated in industrial processes without being put to practical use. The focus in the analysis is placed on the Organic Rankine Cycle technology for utilising LTWHR as a competitive technology for the energy sources where neither gas nor steam cycles offer a technically and/or economically viable solution to generate electric power or other useful energy transformation. Also it is given brief overview of the cycle configurations that are commonly used or proposed in the literature for this kind of applications. Within the analysis is covered waste heat recovery from the exhaust gases from hot water boilers, steam boilers and combined heat and power units
Keywords: waste energy, heat recovery, energy efficiency, organic rankine cycle